1997
DOI: 10.1172/jci119761
|View full text |Cite
|
Sign up to set email alerts
|

Macula densa arginine delivery and uptake in the rat regulates glomerular capillary pressure. Effects of salt intake.

Abstract: These studies tested the hypothesis that delivery and/or cellular uptake of L -arginine limits macula densa nitric oxide generation and actions on tubuloglomerular feedback (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…Intracellular protein hydrolysis releases free ADMA. In exchange for L-arginine and other cationic amino acids, ADMA is transported out of cells through cationic amino acid transporters (CAT) (Baylis, 2006;Closs et al, 1997;Welch and Wilcox, 1997) where it can have effects at sites distal from its production. Although we are not aware of any studies demonstrating an effect of CS on PRMT expression or function, Zhang et al (2006) reported a significant reduction in the expression of CAT1 in human endothelial cells following a brief exposure to 10% CSE.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular protein hydrolysis releases free ADMA. In exchange for L-arginine and other cationic amino acids, ADMA is transported out of cells through cationic amino acid transporters (CAT) (Baylis, 2006;Closs et al, 1997;Welch and Wilcox, 1997) where it can have effects at sites distal from its production. Although we are not aware of any studies demonstrating an effect of CS on PRMT expression or function, Zhang et al (2006) reported a significant reduction in the expression of CAT1 in human endothelial cells following a brief exposure to 10% CSE.…”
Section: Discussionmentioning
confidence: 99%
“…However, an increase in DDAH-2 in the juxtaglomerular apparatus could reduce local levels of ADMA, including within the macula densa cells. nNOS is expressed heavily in macula densa cells where it blunts vasoconstriction of the adjacent renal afferent arteriole, for example by the TGF process, thereby increasing the nephron GFR (212,220). NO generated by macula densa nNOS is implicated in the regulation of renal hemodynamics, for example the renal vasodilation accompanying high salt intake (219).…”
Section: Expression and Function Of Ddah In Diseasementioning
confidence: 99%
“…NO generated by macula densa nNOS is implicated in the regulation of renal hemodynamics, for example the renal vasodilation accompanying high salt intake (219). Microperfusion of ADMA into the macula densa segment of the rat nephron enhances TGF and reduces glomerular capillary pressure by a mechanism that apparently entails inhibition of NOS since it can be prevented by microperfusion of L-arginine (212). Thus upregulation of DDAH-2 in the macula densa cells of the Fig.…”
Section: Expression and Function Of Ddah In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…SDMA does not inhibit NOS but, like the other methylarginine analogues, can compete with arginine for cellular uptake via system y ϩ (3,4). ADMA increases the tone of rat aortic rings (5), raises blood pressure in guinea pigs (6), and reduces resting forearm blood flow in humans (6).…”
mentioning
confidence: 99%